2015
DOI: 10.1002/jbmr.2585
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in Bone Largely Predict Aortic Calcification in an Alternative Rat Model Developed to Study Both Vascular and Bone Pathology in Chronic Kidney Disease

Abstract: Because current rat models used to study chronic kidney disease (CKD)-related vascular calcification show consistent but excessive vascular calcification and chaotic, immeasurable, bone mineralization due to excessive bone turnover, they are not suited to study the bone-vascular axis in one and the same animal. Because vascular calcification and bone mineralization are closely related to each other, an animal model in which both pathologies can be studied concomitantly is highly needed. CKD-related vascular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…In comparison, the 0.25% adenine‐induced CKD model demonstrated only moderate vascular calcification, and significant bone pathology after 8 weeks of adenine treatment. This report was the first to demonstrate these major complications in the adenine model of induced CKD …”
Section: Bone and Mineral Disorders In 025% Adenine‐induced Ckd Modelmentioning
confidence: 64%
See 1 more Smart Citation
“…In comparison, the 0.25% adenine‐induced CKD model demonstrated only moderate vascular calcification, and significant bone pathology after 8 weeks of adenine treatment. This report was the first to demonstrate these major complications in the adenine model of induced CKD …”
Section: Bone and Mineral Disorders In 025% Adenine‐induced Ckd Modelmentioning
confidence: 64%
“…Vascular calcification and bone pathologies are two complications of CKD that have a major impact on mortality. Neven et al studied markers of CKD in the 0.75% adenine diet model, showing excessive vascular calcification with chaotic and marked bone mineralisation due to excessive bone turnover. In comparison, the 0.25% adenine‐induced CKD model demonstrated only moderate vascular calcification, and significant bone pathology after 8 weeks of adenine treatment.…”
Section: Bone and Mineral Disorders In 025% Adenine‐induced Ckd Modelmentioning
confidence: 99%
“…In the present study, we observed an effect of (OEG 2 ) 2 -IP4 on bone osteoid area. However, it was seen in a CKD/VC rat model in young animals with open growth plates and rapid bone growth that presents a dramatically increased bone turnover with chaotic bone mineralization, making the rats particularly vulnerable to an imbalance between excessive osteoid deposition, subsequent mineralization, and bone resorption 74 . Therefore, this model does not accurately reflect the low to mildly increased bone metabolism in the majority of CKD patients 75 .…”
Section: Resultsmentioning
confidence: 99%
“…A severe CKD develops with the direct consequence of a disturbed mineral balance as reflected by the altered calcium and phosphorus levels and in association with the aberrations in hormonal levels of FGF-23 (PTH was not measured in this study but was reported earlier by our group to be increased in rats with adenine-induced CKD [1]) which in turn induced the well-known and highly undesirable complication of CKD, i.e. mineral and bone disorder (MBD) which is characterized by high turnover bone disease and pathological vessel calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we further developed and characterized our previously described model of CKD-MBD (chronic kidney disease - mineral and bone disorders) [1] and investigated whether it would be usable as a model for CRS type 4, as defined by the Ronco classification [2], i.e. CKD causing cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%